Implementasi Kebijakan Program Kartu Identitas Anak (KIA) di Kelurahan Krembangan Utara Kota Surabaya - Zhahral, Arsyilia; Arif, Lukman (VISA: Journal of Vision and Ideas, 2024)
Population issues continue to be a problem in Indonesia, and population registration is being carried out in Kembangan Utara Subdistrict in Surabaya City. The government's effort to overcome this population problem is by publishing Child Identity Cards (KIA). KIA is organized by the Population and Civil Registration Service (Disdukcapil) in districts/cities throughout Indonesia with the aim of providing population identity to children in Indonesia. Apart from that, the implementation of KIA aims to protect and fulfill children's constitutional rights, which is a national program. The aim of the research is to examine the implementation of the KIA policy at the Population and Civil Registration Service and the Residents of Krembangan Utara Subdistrict, Surabaya City, as well as to provide information on the driving and inhibiting factors for the implementation of the policy. The method used in this research is descriptive and qualitative, and data collection techniques use interview, observation and documentation methods. Secondary data was also obtained from journals and previous research. The results of this research show that the implementation of the KIA policy at the Population and Civil Registration Service in Krembangan Utara Subdistrict, Surabaya City is quite good, but there are still many advantages and disadvantages in terms of communication and resources, implementation and bureaucratic structure. Second, facilities and cooperation with third parties are supporting factors for implementing KIA at the Population and Civil Registry Service, Krembangan Utara Subdistrict, Surabaya City. On the other hand, the inhibiting factor is in the community sector.